Utilization of eye care services among adults in a rural community in Rivers State South-South, Nigeria - Datonjo Alwell George; Godswill Inye Nathaniel (Journal of Clinical Ophthalmology and Research)
Background: The aim of this study was to assess the awareness and utilization of eye care services among adults aged 40 years and above in Ndele, Rivers State. Materials and Methods: It was a community-based descriptive cross-sectional study carried out in Ndele, Rivers State. Eligible subjects were selected using the multistage random sampling method. An interviewer-based self-structured questionnaire was administered to each participant following which ocular examination was performed. Information collected included demographic characteristics, knowledge of available eye care facilities, previous use of eye care services, and barriers to the use of eye care services. Data obtained were analyzed using the statistical package SPSS version 20. Pearson Chi-square test was used to test the relationship between variables. P < 0.05 was considered a statistically significant association between variables. Results: Four hundred and twenty-five subjects participated in the study made up of 240 males (56.5%) and 185 females (43.5%), with an M:F ratio of 1:1.3. The age range was 40–88 years, and the mean age of the subjects studied 53.6 ± 11.2 years. Findings showed that awareness of available eye care services was good 69.2%, whereas utilization of such services was very low 23.1%. Better awareness and rate of utilization were found with a higher level of education (P < 0.001), whereas no significant statistical relationship was found for age (P = 0.245) and sex (P = 0.394) in awareness and age (P = 0.415) and sex (P = 0.089) in utilization. Cost of care was the major reason found for nonutilization of the eye care services. Conclusion: In the studied population, although the awareness of eye care services in the community was good, the utilization of the services was very low, and the cost of care was the major factor reducing utilization. Therefore, there was a need to subsidize the cost of services by the government to improve uptake which will further reduce the magnitude of avoidable blindness in Ndele, Rivers State.